Effects of pretreatment strategies on fertility outcomes in patients with adenomyosis - Moawad, Gaby; Youssef, Youssef; Fruscalzo, Arrigo; Khedhri, Slim; Faysal, Hani; Pirtea, Paul; Guani, Benedetta; Vallée, Alexandre; Ayoubi, Jean Marc; Feki, Anis (Frontiers in Reproductive Health, 2024)
Adenomyosis is a commonly encountered pathology in women of reproductive age and frequently coexists with infertility. The effect of adenomyosis on fertility, particularly on in vitro fertilisation and intracytoplasmic sperm injection outcomes, is not well understood. Various pretreatment modalities have been used to improve pregnancy rates and live birth outcomes; however, because of a lack of high-quality evidence, there is no clear consensus on the best pretreatment option. This review was conducted through a PubMed search aiming to highlight the relationship between pretreatment and fertility in women with adenomyosis. Medical, ablative surgical, and non-surgical therapies were reviewed. According to the current literature, gonadotropin-releasing hormone agonist therapy and placement of a levonorgestrel intrauterine system are two suitable medical pretreatment strategies that can improve the clinical pregnancy rates of patients with adenomyosis. Surgical ablation of adenomyosis can also be beneficial, although surgical management can be challenging. Non-surgical thermal techniques, including high-intensity focused ultrasound ablation, percutaneous microwave ablation, and radiofrequency ablation, are much less invasive techniques that have shown effectiveness in improving fertility. Although evidence remains limited, all these procedures have demonstrated a favourable safety profile. Further studies are needed to better develop these techniques and demonstrate their effectiveness.